Designing triazatruxene-based donor materials with promising photovoltaic parameters for organic solar cells. Issue 45 (22nd August 2019) - Khan, Muhammad Usman; Iqbal, Javed; Khalid, Muhammad; Hussain, Riaz; Braga, Ataualpa Albert Carmo; Hussain, Munawar; Muhammad, Shabbir
Abstract : Five new molecules (M1–M5 ) were designed by structural modification of acceptor moiety (rhodanine-3-acetic acid) of well-known synthesized dye JY05, and their optoelectronic properties are evaluated to be used as donor molecules in organic solar cells. Abstract : To address the increasing demand of efficient photovoltaic compounds for modern hi-tech applications, efforts have been made herein to design and explore triazatruxene-based novel donor materials with greater efficiencies. Five new molecules, namelyM1–M5, were designed by structural modification of acceptor moiety (rhodanine-3-acetic acid) of well known experimentally synthesized JY05 dye (referenceR ), and their optoelectronic properties are evaluated to be used as donor molecules in organic solar cells. In these moleculesM1–M5, triazatruxene acts as a donor unit and benzene spaced different end-capped moieties including 2-(4-(dicyanomethylene)-2-thioxothiazolidin-3-yl)acetic acid (A1), ( E )-2-(4-(1-cyano-2-methoxy-2-oxoethylidene)-2-thioxothiazolidin-3-yl)acetic acid (A2), ( Z )-2-(3′-ethyl-4′-oxo-2, 2′-dithioxo-3′, 4′-dihydro-2′ H, 5 H -[4, 5′-bithiazolylidene]-3(2 H )-yl)acetic acid (A3), ( Z )-2-(4′-(dicyano-methylene)-3′-ethyl-2, 2′-dithioxo-3′, 4′-dihydro-2′ H, 5 H -[4, 5′-bithiazol-ylidene]-3(2 H )-yl)acetic acid (A4) and 2-((4 Z, 4′ E )-4′-(1-cyano-2-methoxy-2-oxoethylidene)-3′-ethyl-2, 2′-dithioxo-3′, 4′-dihydro-2′ H, 5 H -[4, 5′-bithiazolylidene]-3(2 H )-yl)acetic acid (A5) respectively, as acceptor units. The electronic, photophysical and photovoltaic properties of the designed moleculesM1–M5 have been compared with reference moleculeR . All designed molecules exhibit reduced energy gap in the region of 1.464–2.008 eV as compared to reference molecule (2.509 eV). Frontier molecular orbital (FMO) surfaces confirm the transfer of charge from donor to acceptor units. All designed moleculesM1–M5 exhibited an absorption spectrum in the visible region and they were broader as compared to that of referenceR . Especially, M5 with highest λ max value 649.26 nm and lowest transition energy value 1.90 eV was accredited to the strong electron withdrawing end-capped acceptor moiety A5. The highest value of open circuit voltage ( V oc ) 1.02 eV with respect to HOMOdonor –LUMOBTP-4Cl was shown byM5 among all investigated molecules which was 0.15 V larger than reference moleculeR . The designed moleculeM5 is proven to be the best candidate for both electron and hole transport mobilities due to its smallest λ e (0.0212 eV) and λ h (0.0062 eV) values among all studied molecules.